THE ONLINE DISPUTE RESOLUTION IN PANCASILA’S FRAME - Kasmudin Harahap (Jurnal Pembaharuan Hukum, 2021)
Online Dispute Resolution is a solution in resolving problems outside the court where online dispute resolution is an appropriate solution to resolve online trade disputes, the settlement must apply Pancasila values. Method The approach used in this research is normative juridical. The results of the research show that the application of Online Dispute resolution in addition to legal reform in the field of electronic transactions is also related to efforts to create legal certainty in online dispute resolution in Indonesia. The basic principles of online dispute resolution in Pancasila values are reflected in the spirit of kinship and mutual cooperation, these principles is a reflection of Pancasila values leading to basic values which are the elaboration of the same spirit and within the limits allowed by these basic values. Agreed values in realizing the law as the goal of justice and creating justice